Penyelesaian Sengketa Harta Bersama Melalui Akta Perdamaian: (Tinjauan Putusan No. 1700/Pdt.G/2025/PA.Sby) - Indah Purbasari; Febri Khoirul Auni; Moh. Rudi Fajar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The resolution of joint property disputes after divorce is a significant issue in Islamic family law in Indonesia, as it pertains to justice and legal protection for former spouses. One available alternative for settlement is through a Peace Deed (Akta Perdamaian), which results from the parties’ agreement and is ratified by the religious court judge. This study employs a qualitative approach using a case study method on the Decision of the Religious Court of Surabaya No. 1700/Pdt.G/2025/PA.SBY. The findings show that the Peace Deed is an effective instrument for resolving joint property disputes quickly, efficiently, and without prolonged litigation. Professionally conducted mediation plays a crucial role in reaching a fair and balanced agreement. Moreover, the court’s ratification of the agreement grants the Peace Deed binding legal force and allows for execution in case of non-compliance. This mechanism also helps reduce post-divorce emotional conflict and maintains good relations between parties. This study illustrates how the Peace Deed can serve as an alternative solution for resolving joint property disputes and offers recommendations for courts to optimize the role of mediation and expand public awareness about the benefits of dispute resolution through peaceful agreements.